Dissection of Larval and Pupal Wings of Bicyclus anynana Butterflies - Banerjee, Tirtha Das (Methods Protoc, 2020)
The colorful wings of butterflies are emerging as model systems for evolutionary and developmental studies. Some of these studies focus on localizing gene transcripts and proteins in wings at the larval and pupal stages using techniques such as immunostaining and in situ hybridization. Other studies quantify mRNA expression levels or identify regions of open chromatin that are bound by proteins at different stages of wing development. All these techniques require dissection of the wings from the animal but a detailed video protocol describing this procedure has not been available until now. Here, we present a written and accompanying video protocol where we describe the tools and the method we use to remove the larval and pupal wings of the African Squinting Bush Brown butterfly Bicyclus anynana. This protocol should be easy to adapt to other species.